RF Simulations for AAβ Cryptosystem, an Asymmetric Encryption Scheme - Syed Farid Syed Adnan; Mohd Anuar Mat Isa; Habibah Hashim (Institute of Advanced Engineering and Science, 2018)
Internet of Things (IoT) is a way of providing data with the physical thing that interconnected to the network, which is the Internet. The IoT devices connected to the internet, broadcast of the data to the broker or a server, becomes an open route for attackers to gain the data and making the data becomes vulnerable. Thus, the data could be altered or spoofed by an attacker which led to security issues especially on data integrity. Therefore, the data security collected from the sensors is as important as on the servers that eventually become the big data. However, most sensors are low powered devices in term of CPU, storage, memory and batteries that cryptographic algorithm computations might give overhead to the sensors and reduce the batteries even faster than it is supposed to be. Instead of looking at symmetric encryption scheme, this paper tries to explore the capabilities of the asymmetric scheme on resource constrained devices communications. Thus, this paper presents an RF communication analysis of a low consumption asymmetric encryption, the AAβ (AA-Beta) that promising to implement on the IoT devices to secure the IoT networks. The result shows only 14% size increased in ciphertext from plaintext and the RF simulation communications show a better result in Raspbian OS environment compare to windows environment even though with same configurations